From the Concept of Sustainable Development to the Subsidies of Agricultural Environmental Management - Gyarmati, Ágnes (Acta Agraria Debreceniensis, 2005)
The most important aim of the study is to introduce the theoretical background of my PhD dissertation – agricultural environmental management –, in order to help the scientific foundations for my dissertation, which is in progress. For this reason I will try to clarify and systematize facts found in the special literature according to my own thoughts, from a new aspect.In my study, I therefore attempt to introduce the theoretical background of sustainable development as pertains to the subsidies of agricultural environmental management (National Agricultural Environmental Management Program, National Regional Development Plan, agricultural environmental management measures). Having clarified the concepts I place sustainable development in the economic theories directed to the treatment of environmental problems, introduce where subsidies are within the environmental regulation implements and I dwell on to the institutional questions in the explanation. I then study questions of sustainable agricultural economics. Accession to the European Union has to be considered as one of the most important concrete motivities of domestically coming into prominence of agricultural environmental subsidies therefore I think it is important to study how the problematic of sustainable development, sustainable agricultural development and agricultural environment protection worked out in the EU. Finally I survey the main characteristics of domestic agricultural environment management programs fitting into the theories explained above, how the program adjusts to the theories of sustainable development and sustainable agricultural development.In the dissertation I begin with sustainable development as the broadest theoretical background, then I survey a narrower category, the theories of sustainable agricultural development and how concrete agricultural environmental programs fit into the studied theoretical relations.